108 Spatially Different Temporal Filtering With X-Ray Attenuator: A Novel Technique of Dose Reduction in Neuroendovascular Interventions. (August 2015) - Sonig, Ashish; Setlur Nagesh, Swetadri Vasan; Natarajan, Sabareesh Kumar; Cress, Marshall C.; Munich, Stephan; Rangel-Castilla, Leonardo; Ionita, Ciprian; Bednarek, Daniel; Snyder, Kenneth V.; Hopkins, L. Nelson; Levy, Elad I.; Rudin, Stephen; et al.
Abstract : INTRODUCTION: Dose reduction during fluoroscopy is of paramount importance. Our center has developed a novel patient-dose-savings technique for image-guided neurovascular interventions, involving a combination of a material x-ray region-of-interest (ROI) attenuator and spatially different temporal filtering. Our technique gives real-time full field-of-view as against some previous techniques of restricted view (spot fluoroscopy). We present our comparative clinical experience with standard flat panel angiography (FPA) and our technique (ROI-FPA). METHODS: Patient data (under IRB approval) from 10 patients (4 middle cerebral artery, 5 anterior communicating artery, and 1 cavernous internal carotid artery aneurysms) were acquired using rotational digital subtraction angiography and computed tomographic angiography for 3-dimesional (3-D) rendering and processing. 3-D models were generated using an Eden-260V-3-D-printer (Object-Stratasys). We performed primary coiling on the models (Figure 1) using a Toshiba Infinix C-arm. The dose incident to the patient is reduced by using a 0.7-mm-thick copper attenuator with a circular ROI hole in the middle. The attenuator is mounted inside the x-ray tube mechanism and can be deployed automatically when needed. Each 3-D printed model was treated twice, using ROI-FPA and standard FPA. A total of 80 images at varied stages of intervention were acquired. Each image was shown twice to 2 neurointerventionists and the images were rated individually. A total of answers to 400 questions (Table 1) based on visibility of aneurysm, proximal and distal vasculature, microwire, coil, and guide tip were scored. The intrarater agreements are measured by Kendall-τ-β correlation coefficient and the interrater agreements are measured by κ statistics. RESULTS: For the thickness and size of the ROI attenuator used, a total integral dose reduction of 68% was achieved. The mean scores obtained in the images when ROI was applied did not differ significantly from standard FPA images, suggesting similar image quality. The intra-rater agreement varied from (Kendall τ0.14-1) and interrater (κ0.16-0.52). CONCLUSION: Our study has shown that a significant dose reduction could be achieved without compromising the image quality during neuroendovascular interventions.